Fusel Oil as A Fuel Additive with Gasoline to Operate Spark Ignition Engine, A Comparative Review - Maha A. Taha; Obed Ali; Musa M. Weis (NTU Journal of Engineering and Technology)
The climate change, global warning, energy price, and energy supply crisis are the essential issues facing of the world. The petroleum based energy supplement was the main responsible for these problems.  Alternative fuels need and the increasing of the sources of renewable and clean energy with limited fuel supplies are becoming important. Many students are studies alcohol as alternative fuels. From fermentation process fusel oil is produced as a byproduct with higher alcohol content. During the last decades,  fusel oil is took care as a renewable fuel in spark ignition engine. The objective of the present study, is to survey the effects of fusel oil-gasoline mixture on the performance (break torque, break power, brake specific fuel consumption, efficiency, & effective) also on characteristics of combustion and emissions ((CO , HC hydrocarbons, NOx)) in SI engine.